Ответ(ы) на вопрос:
Гость
[latex]\frac{y}{x^2-y^2}:(\frac{y}{x-y}+\frac{x}{x+y})=\\ \frac{y}{x^2-y^2}:\frac{y(x+y)+x(x-y)}{x^2-y^2}=\\ \frac{y}{x^2-y^2}:\frac{yx+y^2+x^2-xy)}{x^2-y^2}=\\ \frac{y}{x^2-y^2}:\frac{y^2+x^2}{x^2-y^2}=\\ \frac{y}{x^2-y^2}*\frac{x^2-y^2}{x^2+y^2}=\\ \frac{y}{x^2+y^2}[/latex]
Гость
Выражение: y/x^2-y^2:(y/x-y+x/x+y) Ответ: y/x^2-y^2:(y/x+1) Решаем по действиям:
1. x/x=1
2. -y+y=0 Решаем по шагам:
1. y/x^2-y^2:(y/x-y+1+y)
1.1. x/x=1
2. y/x^2-y^2:(y/x+1)
2.1. -y+y=0
Не нашли ответ?
Похожие вопросы